Pengaruh Implementasi Standar Akuntansi Pemerintahan Berbasis Akrual Dan Efektivitas Fungsi Pengawasan Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten Aceh Besar - Iin Novianti; Mr. Syamsidar; Cut Fitrika Syawalina (BALANCE: Economic, Business, Management and Accounting Journal, 2018)
ABSTRACT   The purpose of this study was to determine the effect of the implementation of accrual based government accounting standards and the effectiveness of supervisory functions on government financial performance in Great Aceh district.The sample in this study were 81 people from the total population. In data collection the researchers used questionnaires, and analysed the data qualitatively and quantitatively. The data analysi to find out the effect of the dependent and independent variables by using a multiple regression equation analysis. Test the hypothesis by using t-test, with the help of computer V.22.0 SPSS program for windows.The results showed a positive linear relationship and quite tightly between the  implementation of accounting governance standards based on accruals and the effectiveness of supervision functions on accountability of lo  oversight of the financial performance of local government in Aceh Besar district. Further to the positive and significant influence of each independent variable on the financial performance of government in Great Aceh district.It is necessary to accelerate the implementation of activities that have been budgeted previously, moreover the training that has been held should put forward the practice of the field to meet the human resource needs, while in the aspect of science and technology needed to accelerate the development of financial applications in order to produce the financial reports on an accrual basis.Keywords : the implementation of accrual based government accounting standards, the effectiveness of supervisory functions, the financial performance of local governmentCorrespondence to : muhammad.arafah95@gmail.comABSTRAK  Tujuan penelitian ini adalah untuk mengetahui pengaruh implementasi standar akuntansi pemerintahan berbasis akrual dan efektivitas fungsi pengawasan terhadap kinerja keuangan pemerintah daerah kabupaten Aceh Besar. Sampel dalam penelitian ini sebanyak 81 orang dari seluruh total populasi. Pengumpulan data menggunakan kuesioner,dan analisa secara kualitatif dan kuantitatif. Analisis data untuk melihat pengaruh variabel terikat dengan variabel bebas menggunakan analisis persamaan regresi berganda. Uji hipotesis menggunakan uji statistik t-test,dengan bantuan program komputer program SPSS V.22.0 For windows.Hasil penelitian memperlihatkan hubungan linier positif dan berhubungan cukup erat antara implementasi standar akuntansi pemerintahan berbasis akrual dan efektivitas fungsi pengawasan terhadap kinerja keuangan pemerintah daerah kabupaten Aceh Besar. Selanjutnya terdapat pengaruh positif dan signifikan dari masing-masing variabel bebas terhadap kinerja keuangan pemerintah daerah kabupaten Aceh Besar.Perlu adanya percepatan pelaksanaan kegiatan-kegiatan yang telah dianggarkan sebelumnya, selain itu diklat yang diadakan harus lebih mengedepankan praktek di lapangan untuk memenuhi kebutuhan SDM, sedangkan dalam aspek IT diperlukan percepatan pengembangan aplikasi keuangan agar dapat menghasilkan laporan keuangan secara akrual.Kata kunci : Implementasi standar akuntansi pemerintahan berbasis akrual, efektivitas fungsi pengawasan, kinerja keuangan pemerintah daerahKorespondensi :muhammad.arafah95@gmail.com